Modelling and Control of Air Bellow based Active Suspension System. Issue 1 (December 2020) - Muthukumar, M; Arjun, S V; Saravanakumar, D; Sakthivel, G; Jegadeeshwaran, R
Abstract: This paper presents a complete design and simulation of active suspension actuated using pneumatic air bellow. The electronic controlled active suspension will control all vertical force acting from road surface by regulating the air mass of bellow. Quarter car active suspension is modelled and analysed using Matlab-Simulink. The output of designed active suspension system is simulated under standard road input that gives the response of the suspension to varied roughness of road surface. From the results it is evident that proposed active suspension system can suppress more than 60% than standard passive suspension system.